Occupational hazards among laboratory hub riders in selected health centres in central region of Uganda - Agondeze, Sandra; Kizza, Stephen S.; Vuzi, Peter; Ddamulira, Christopher (Direct Research Journal of Public Health and Environmental Technology, 2021)
Laboratory hub riders (LHRs) are motorcycle riders employed by health centres to handle, package, and transport biological samples within and between different health centres. Their nature of work exposes them to infectious microorganisms through accidental splash exposure or sharps injuries. The study was carried out in selected health centres in Central region, Uganda. The objective was to assess the factors influencing Occupational hazards. The population of the study was 140 LHRs proportionately allocated in selected Health centres in central region of Uganda, with a sample size of 103 LHRs. It was a cross sectional study using both quantitative and qualitative methods. Data were analysed using descriptive statistics to derive means, frequencies and standard deviations as well as inferential statistics to derive odds ratios and significances using logistic regression and multivariate analysis. The study revealed that majority of the LHRs was youths, aged 20-35 years, with Ordinary level certificate as their highest level of education. About 63.7% reported occupational exposure occurrences to management, and were knowledgeable about risks and hazards at work place. Majority 92.2% viewed their jobs as high risk and used Personal Protective Equipment (PPE) 85.4%, to reduce occupational hazards. Very few 12.3 % of the LHRs received training before commencing with their duties as new recruits. The prevalence of occupational hazards was quite low with 36.9% reported having experienced splash exposures, and 7.8% reported having experienced sharps injuries in the past 12 months. Job specific training was found to be the influential factor for occupational hazards in regard to splash exposure (Adjusted Odds Ratio (AOR) = 0.33, 95% Confidence Interval (CI) = 0.12 - 0.93, p-value (p) = 0.04) and sharps injuries (AOR = 0.56, 95% CI = 0.73 - 0.66, p = 0.01). There is need for health centres to incorporate job specific training such as safety precautions on infection prevention and control for newly recruited LHRs before they commence with their duties.
Keywords: Occupational hazards; Laboratory hub riders; Health centres; Uganda